Optimizing Organizational Performance: Unraveling the Interplay of Psychological Attributes in the Era of New Ways of Working - Musthofa, Zainul; Raj, Yeshwant (Southeast Asian Business Review, 2023)
The global proliferation of New Ways of Working (NWW) has accelerated, driven by technological advancements and the exigencies of the COVID-19 pandemic, compelling a substantial workforce to adopt teleworking. However, the commonplace nature of NWW has ushered in a new challenge: the mental well-being of employees worldwide. Consequently, the psychological attributes of employees assume paramount significance for organizations striving to sustain their operations. This study endeavors to scrutinize the pivotal role of psychological attributes in the efficacious implementation of teleworking, with a consequential impact on organizational performance. Employing the production of space theory, the research elucidates the intricate dimensions inherent in NWW. Methodologically, a multilevel analysis is employed to unravel the intricate interplay of variables at both individual and organizational levels. The survey, conducted among individuals in Southeast Asia with teleworking experience during the pandemic, amassed 319 samples primarily from Indonesia. The findings underscore the substantial influence of self-efficacy, entitlement, and resilience on the successful adoption of NWW. Additionally, the study employs the PROCESS macro by Hayes to meticulously validate both mediating and moderating relationships. The outcomes accentuate the pivotal role of work engagement as a moderator, facilitating direct impacts of psychological variables on NWW and indirect effects on firm performance, mediated through NWW. This research contributes nuanced insights into the multifaceted dynamics of teleworking, offering a sophisticated understanding of the interplay between psychological attributes, NWW, and organizational performance in the contemporary landscape.